Cyto-histological correlation of salivary gland lesions- a prospective study in a tertiary care institute - Negi, Soma; Mardi, Kavita; Sood, Shivani; Gupta, Neelam; Mohindroo, N. K.; Kumar, Muninder; Azad, Ramesh; Chaudhary, Ashish; Negi, Gunjita (International Journal of Research in Medical Sciences, 2022)
Background: Fine needle aspiration cytology (FNAC) has an essential proven role in diagnosing most of the common and benign salivary gland lesions. However, limited cellularity and morphological heterogeneity of the lesion can pose diagnostic challenges. The present study was conducted in a tertiary care centre over a period of one year with an objective to study the cyto-morphological features of salivary gland lesions and correlate cytological findings with histopathology. Methods: The study was carried out over a period of one year from January 2014 to December 2014. FNA specimens obtained from 78 patients were analyzed. Of these, only 51 patients underwent biopsy or surgery and their specimens were subjected to histopathological examination. Validation of cytological diagnosis was done on the basis of histopathological diagnosis. Results: A total 78 patients with salivary gland lesions were subjected to FNAC. Non neoplastic lesions constituted 19 cases (25%) and benign lesions constituted 46 cases (80.70%). Malignant lesions constituted 11 cases (19.30%). Two cases were inconclusive due to inadequate aspirated material. Overall sensitivity, specificity and diagnostic accuracy were 95.98%, 99.20% and 98.09% respectively. Conclusions: FNAC continues to be an accurate diagnostic technique in the hands of an experienced cytopathologist. It is a highly sensitive and specific technique for rapid diagnosis of most of the salivary gland swellings.